Underdiagnosis of enamel defects in Family Health Centres of Talca city, Chile - Carla Orellana-Herrera; Karla Bascuñan-Yañez; Karla Gambetta-Tessini; Vidal Pérez-Valdés (Universidad de Concepción., 2020)
Enamel defects (i.e. hypoplasia, diffuse and demarcated opacities), in particular Molar Incisor Hypomineralization (MIH), are alterations of dental enamel with underlying implications in affected children. A proper diagnosis and clinical dental records are needed to improve clinical management of enamel defects in primary health setting. This cross-sectional study aimed to determine the prevalence of enamel defects in 6-year-old children attending to Family Health Centres in Talca city and comparing the clinical diagnosis with that registered by general dental practitioners (GDPs) on the clinical dental records. Children (n=318) were evaluated by a calibrated examiner using the modified DDE index criteria. Almost half of children had enamel defects (47.5%; n=151). The proportion of children affected by demarcated opacities (36.8%; n=117) was higher than those effected by hypoplasia (13.8%; n=44) and diffuse opacities (12.6%; n=40). MIH prevalence was 19.8% (n=63) and 22% (n=14) of MIH-affected children presented the severe form. Clinical dental records registered by GDPs recorded 6.6% (n=10) of enamel defects, but the type of defect was not consistent with the clinical examination undertaken by the calibrated examiner. These findings suggest that enamel defects are prevalent in the studied population, but only few cases were registered in clinical dental records. To achieve diagnosis consensus, the registration section for enamel defects in the clinical dental record at Family Health Centres may need some improvement. Further diagnostic training for GDPs working in the public sector may also be necessary.